A University in Zion: Max Weber and Gershom Scholem on Jewish Eschatology and Academic Labor. (December 2022) - Almog, Yael
Abstract : In his "Science as Vocation, " Weber equates rational academic conduct with Jewish ethics. For Weber, the Jewish tradition, which separates moral conduct from messianism, is emblematic of scientists' strenuous distinction of empiricism from metaphysics. The emergence of a Zionist university in Jerusalem, an institute that was positioned as a part of a Jewish nation-building project, complicated this parallel. This article examines Gershom Scholem's activist approach to Jewish studies as a fundamental revision of the Weberian model of scholarship with the significant role that this model destines to the Jewish tradition. Scholem's vision of scholarship at the Zionist university constitutes Jewish eschatology as a pillar of a scholastic national tradition. Scholem's portrayal of Jewish messianism as an insular tradition overturns Weber's portrayal of Jewish ethics as a lesson for Western academia. Reading Scholem with Weber shows that the enterprise of founding a university in Jerusalem ran counter to European liberal conceptions of Judaism. Moreover, reading them together shows Scholem's notion of academic labor to reinstitute a separatist theological ethos as a formative model for scholarship.